Profil Gonad Kodok Lembu Betina yang Diberi Human Chorionic Gonadotropin dan Ekstrak Hipofisis Kodok Lokal - Mudite Adnyane, I Ketut; Tiara Ilham, Sevy; Agil, Muhammad (Jurnal Veteriner, 2012)
Bulllfrog (Rana catesbeiana) are naturally reach sexual maturity at the age of 3 years aftermetamorphosis. This research aims to study the gonad growth of female bullfrog. given human chorionicgonadotropin (hCG) and hipofise extract of local frog in order to accelerate the maturity. There were 40female bullfrog used in this study and divided into four treatment groups and one control. The treatmentswere injections of 150 IU hCG, 200 IU hCG, 8 hipofise, 16 extract of hipofise and controls. The injectionswere conducted once a month for four months. Every month after the first injection, two of bullfrogs fromeach group were measured their body and gonad weight, in addition, the stage of ovary was also observedeither in macroscopically and microscopically. The results showed that hCG treatment group gave betterresults compared with the treatment of hipofise extract of local frog. The injection of 200 IU hCG gave thebest result of gonad maturity index (IKG) 4.9%, compared with other treatment groups. Giving a dose of200 IU hCG and 16 hipofise exctract of local frog can be used to accelerate the maturity of female bullfrog
Keywords: bullfrog, gonad, hCG, hipofise.